Telemedicine diagnosis of cytomegalovirus retinitis by nonophthalmologists - Yen,M. (American Medical Association, 2015)
Copyright 2014 American Medical Association. All rights reserved. IMPORTANCE: Cytomegalovirus (CMV) retinitis continues to be a leading cause of blindness in many developing countries. Telemedicine holds the potential to increase the number of people screened for CMV retinitis, but it is unclear whether nonophthalmologists could be responsible for interpreting fundus photographs captured in a telemedicine program. OBJECTIVE: To determine the accuracy of nonophthalmologist photographic graders in diagnosing CMV retinitis from digital fundus photographs. DESIGN, SETTING, AND PARTICIPANTS: Fifteen nonexpert graders each evaluated 182 mosaic retinal images taken from the eyes of patients with AIDS who were evaluated at the Ocular Infectious Diseases Clinic at Chiang Mai University in Chiang Mai, Thailand. MAIN OUTCOMES AND MEASURES: Graders diagnosed each image as CMV retinitis present, CMV retinitis absent, or unknown. The results from each grader were compared with those of an indirect ophthalmoscopic examination from an experienced on-site ophthalmologist as well as with the consensus grade given by a panel of CMV retinitis experts. RESULTS: Relative to the on-site ophthalmologist, the sensitivity of remote CMV retinitis diagnosis by nonexpert graders ranged from 64.0%to 95.5% (mean, 84.1%; 95% CI, 78.6%-89.6%)), and the specificity ranged from 65.6%to 92.5% (mean, 82.3%; 95% CI, 76.6%-88.0%)). Agreement between nonexpert and expert graders was high: the mean sensitivity and specificity values of nonexpert diagnosis using expert consensus as the reference standard were 93.2% (95% CI, 90.6%-95.8%) and 88.4% (95% CI, 85.4%-91.1%), respectively. Mean intrarater reliability also was high (mean Cohen κ, 0.83; 95% CI, 0.78-0.87). CONCLUSIONS AND RELEVANCE: The sensitivity and specificity of remote diagnosis of CMV retinitis by nonexpert graders was variable, although several nonexperts achieved a level of accuracy comparable to that of CMV retinitis experts. More intensive training and periodic evaluations would be required if nonexperts are to be used in clinical practice.